(untitled) (Jurnal Ampere, 2025)
This study evaluates the techno-economic feasibility of RDF-based and hybrid RDF–PV power systems in Pulogadung Industrial Area through five configuration scenarios. Simulations using Homer software assessed LCOE, NPV, fuel consumption, and emissions of CO₂, CO, and particulate matter. Results indicate a trade-off between PV capacity, RDF consumption, and LCOE: increasing PV penetration reduces RDF consumption and emissions but tends to raise LCOE. Among the scenarios, Scenario C (hybrid RDF–PV with 10% PV load) provides the best balance between energy cost, fuel consumption, and emissions, with an NPV of IDR 408 billion, LCOE of IDR 5,852/kWh, RDF consumption of 2,435 tons/year, CO₂ emissions of 379 kg/year, CO 39.8 kg/year, and particulate matter 0.241 tons/year. These findings confirm that integrating RDF power plants with PV is a sustainable solution for industrial waste management and energy supply, with potential for replication in similar industrial areas.